2018
DOI: 10.4103/ijps.ijps_31_17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of compound muscle action potential generated by donor nerves with the recovery of elbow flexion in Oberlin transfer in brachial plexus injury

Abstract: Objective:To study the correlation of compound muscle action potential of donor nerves with the recovery of elbow flexion in Oberlin transfer in brachial plexus injury.Introduction:Distal nerve transfer using motor fascicle of ulnar or median nerve to restore elbow flexion is a part of reconstructive surgery after upper brachial plexus injury, first described by Oberlin et al. However, one of the most critical influences on functional outcome is number of functioning motor axons in donor fascicle which is refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We have shown that CMAP of donors corelates well with elbow flexion outcome in adult palsies and follow this concept in babies too. 10…”
Section: Indications For Primary Plexus Surgerymentioning
confidence: 99%
“…We have shown that CMAP of donors corelates well with elbow flexion outcome in adult palsies and follow this concept in babies too. 10…”
Section: Indications For Primary Plexus Surgerymentioning
confidence: 99%